The effects of immigration on housing prices in the greater Reykjavík area - Björn Steinar Birgisson 1996- (2021)
This study aims to analyze the impact of immigration on housing prices in the greater Reykjavík area in Iceland. Similar studies performed around the world have found evidence that point to either negative or positive effects of immigration on housing prices. Three regression analyses were performed, one analysis was for single-family housing in the greater Reykjavík area, another analysis was for multi-family housing in the greater Reykjavík area. The final analysis was for multi-family housing in Efra-Breiðholt, which consists of a high population of immigrants. That analysis was performed since some previously published literature indicated that areas with a high share of immigrant population see lower housing price rises or even price reductions, compared to areas with lower immigrant populations. Ordinary least squares multiple regression analyses were used to assess the effect of immigration on housing prices. Data for the analyses was collected from Registers Iceland, Statistics Iceland and the Central Bank of Iceland. The results of the analyses indicated strongly that increased immigration has a positive effect on housing prices. The results for the greater Reykjavík area indicated that the effect of immigration was higher for multi-family housing, compared to single-family housing. Finally, while the results of the analysis of multi-family housing in Efra-Breiðholt also indicated that increased immigration had a positive effect on housing prices there, however the effect of immigration in that analysis was lower than in the other two analyses. Additionally, decreases in indexed mortgage rates and the stock index was found to have a positive effect on housing prices in the analysis of single-family housing in the greater Reykjavík area and increases in purchasing power was found to have a positive effect on housing prices in Efra-Breiðholt.